Community Service Activities – Counseling and Waist Circumference Screening in the Context of Early Detection of Obesity in Adolescent Boys - Alexander Halim Santoso; Ernawati Ernawati; Sukmawati Tansil Tan; Yohanes Firmansyah; Alicia Sarijuwita; Jasmine Syabania Noviantri (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
Counseling activities and waist circumference screening in the context of early detection of obesity in male students aim to increase awareness of the importance of maintaining health and preventing obesity among male students. This activity was carried out using a combination approach between counseling and waist circumference screening. The counseling was conducted to provide a better understanding of the risk of obesity and the importance of measuring waist circumference as an indicator of health. Boys were given information about the negative impact of obesity on physical and psychological health, as well as the importance of a healthy lifestyle and a balanced diet. In addition to counseling, this activity also involves screening waist circumference as a method for early detection of the risk of obesity. Boys' waist circumference was measured using a measuring tape, and the measurement results were compared with a predetermined reference standard. This helps identify students who are in the waist circumference range who are at risk and require further follow-up in obesity prevention and management. The results of this activity show that male students need to understand the importance of maintaining health and managing their weight well. Waist circumference screening provides useful information in evaluating the risk of obesity in male students. In efforts to prevent and control obesity, collaboration between families, educators and medical personnel is very important to provide the necessary support, understanding and guidance